(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the epidemiological, clinical, and paraclinical characteristics of Candida-induced fingernail onychomycosis. Subjects and methods: A cross-sectional descriptive study was conducted on 65 patients diagnosed with fingernail onychomycosis due to Candida at the National Hospital of Dermatology and Venereology from December 2024 to May 2025. Results: The study population showed a female predominance (78.5%) compared to males (21.5%). The most common age group was 40-59 years (44.6%), with the majority of patients residing in urban areas (66.1%). The most frequently reported occupations were housewives (24.6%) and office workers (21.5%). The most common risk factor was frequent exposure to water and chemical agents (67,7%). Clinical features observed included nail thickening (90.8%), bilateral hand involvement(70.8%), nail splitting/fracturing(63.1%), paronychia(44.6%). Fungal culture results identified the following Candida species: Candida albicans (43.1%), Candida tropicalis (32.3%), Candida glabrata (9.2%) Candida krusei (9.2%). Conclusion: Fingernail onychomycosis caused by Candida primarily affects middle-aged women, characterized clinically by nail thickening, splitting/fracturing and paronychia. Frequent exposure to water and chemicals is a major risk factor. Candida albicans and Candida tropicalis were the most commonly isolated species, highlighting the importance of accurate species identification to improve treatment outcomes.